The use of convolutional code for narrowband interference suppression in OFDM-DVBT System - Abdullah, Aizura; Jamal, Muhammad Sobrun Jamil; Abdullah, Khaizuran; Ismail, Ahmad Fadzil; Asnawi, Ani Liza (Asian Research Publishing Network, 2014)
The problem of mitigating narrowband interference (NBI) due to coexistence between Digital Video Broadcasting-Terrestrial (DVB-T) and International Mobile Telecommunication-Advanced (IMT-A) system is considered. It is assumed that a spectrum of IMT-A system between 790-862 MHz interfere the spectrum of the OFDM signal in DVB-T band. Two types of convolutional code (CC) which are non-systematic convolutional code (NSCC) and recursive systematic convolutional code (RSCC) are proposed to mitigate NBI. The performance of the two techniques is compared under additive white Gaussian noise (AWGN) channel. It is observed that NSCC has a better bit error rate (BER) performance than RSCC. The result showed good performance for low SNR (≤ 5dB.